Mock jurors’ expectations regarding the psychological harm experienced by rape victims as a function of rape prototypicality - Pickel, Kerri L. (Psychology, crime & law, 2017)
We examined mock jurors’ judgments in a rape case that was either prototypical (late-night assault by a stranger in a public place) or non-prototypical (daytime assault by an acquaintance in a private home). We also varied the psychological harm experienced by the victim as a result of the rape (mild anxiety or posttraumatic stress disorder (PTSD)). We hypothesized that participants’ expectations regarding the level of harm the victim is likely to experience would mediate the effect of harm level on ratings of the victim’s credibility, and this indirect effect would be contingent on the prototypicality of the case. In a pilot experiment we demonstrated that people expect prototypical rape cases to be more traumatic for victims than non-prototypical cases. In the main experiment, and as predicted, participants in the Prototypical condition expected the victim to develop PTSD more than mild anxiety, but Non-Prototypical condition participants expected the opposite. In addition, a level of harm that was consistent rather than inconsistent with their expectations led participants to rate the victim as more credible; they also rated her as less responsible for what happened, and they thought the defendant was more likely guilty and that he should be incarcerated for a longer period of time.